A novel chaotic image encryption algorithm using block scrambling and dynamic index based diffusion - Xu, Lu; Gou, Xu; Li, Zhi; Li, Jian (Optics and lasers in engineering, 2017)
In this paper, we propose a novel chaotic image encryption algorithm which involves a block image scrambling scheme and a new dynamic index based diffusion scheme. Firstly, the original image is divided into two equal blocks by vertical or horizontal directions. Then, we use the chaos matrix to construct X coordinate, Y coordinate and swapping control tables. By searching the X coordinate and Y coordinate tables, the swapping position of the processing pixel is located. The swapping control table is used to control the swapping of the pixel in the current block or the other block. Finally, the dynamic index scheme is applied to the diffusing of the scrambled image. The simulation results and performance analysis show that the proposed algorithm has an excellent safety performance with only one round. •A novel chaotic block image encryption algorithm is proposed.•The proposed scrambling scheme can also be well used for double image scrambling.•A two dynamic indexes based diffusion scheme is proposed.•The proposed algorithm can resist chosen- and known-plaintext attacks effectively.•The proposed algorithm has an excellent encryption performance with only one round.